A new species of the genus Oxyporus Fabricius (Coleoptera: Staphylinidae: Oxyporinae) in Yunnan Province, China - Li, Guo-Feng; Wang, Chun-Mei; Li, Hua-Feng; Li, Zhi-Gang; Huang, Pu-Ze (Zootaxa, 2017)
Oxyporus (Oxyporus) wangae sp. nov. is described from Yunnan, China. Color images of the habitus and aedeagus of the new species are included. A key to the genus Oxyporus of Yunnan Province species is provided.